Feasibility study of Composite Field Effect Transistor (COMFET) in submicron devices - Farooq S.F.S.; Hamid F.A. (2023)
A linear transconductor is highly desirable in many applications such as continuous time filtering and ADC. In long channel devices where the I-V characteristic of the transistor follows the square law, COMFET circuit achieves linearity without the need to invoke small signal. This paper studies the feasibility of implementing COMFET at submicron length where transistor do not follow square law and a variety of second order effects degrade the linearity of COMFET. The simulated THD at 1 kHz of COMFET and other transconductors are compared.